To start, we know that the equation we are trying to find is a straight line. It hits the x-axis at -3 and the y-axis at -1.
Thus, we know that the line passes through (0, -1) and (-3, 0).
We can now find the gradient using the gradient form: [tex]\frac{y_1 - y_2}{x_1 - x_2}[/tex]
Thus, the gradient becomes: [tex]m = \frac{0 - (-1)}{-3 - 0}[/tex]
[tex]m = -\frac{1}{3}[/tex]
Since we have a point of interest and a gradient, we can use the point-gradient form of a straight line to find the equation of the straight line.
[tex]y - y_1 = m(x - x_1)[/tex]
Use either the y-intercept or the x-intercept as your point.
[tex]y + 1 = -\frac{1}{3}(x - 0)[/tex]
[tex]y + 1 = -\frac{1}{3}x[/tex]
Thus, the equation becomes:
[tex]y = -\frac{1}{3}x - 1[/tex]
Now, since the shaded region is below the line, we know that the inequality becomes:
[tex]y \leq -\frac{1}{3}x - 1[/tex]
But, since it's dotted, we need to exclude the line itself.
Thus, the inequality becomes:
[tex]y < -\frac{1}{3}x - 1[/tex]